THE EFFECT OF USING SMARTPHONES ON THE LEARNING ACHIEVEMENT OF CLASS XI MIPA SMA KARTINI UTAMA STUDENTS - Yuhani, Yuhani; Fatmawati, Fatmawati; zailani@umsu.ac.id, zailani@umsu.ac.id (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to examine whether there is an influence of the use of smartphones on student achievement in SMA Kartini Utamain the Department of Mathematics and Natural Sciences class XI. Sampling using simple random sampling technique. The sample taken was MIPA 1 class XI with 36 students. This study uses one independent variable, namely the use of smartphones (X) and one dependent variable, namely learning achievement (Y). The data used in this study are primary data in the form of questionnaires with 36 respondents and secondary data in the form of average report cards. This research method uses ex post facto. The data analysis technique used in this study is simple regression analysis. The results of this study note the significance value (Sign.) of 0.416, which means greater than 0.05. In addition to the independent variable (smartphone usage), tcount = 0.823 2.0322 = ttable is obtained. So it can be concluded that H0 is accepted and Ha is rejected which means there is no significant effect between smartphone usage (X) on student achievement (Y).